Synchronization Between Election Campaign Regulations and University Autonomy Rules - Nabilah Qonita Maharani; Imran Imran; Mohammad Safrin (Rechtsvinding, 2026)
The Constitutional Court's decision that allows election campaigning in academic settings sparks an existential dilemma for educational institutions, where the line between maintaining political neutrality and upholding campus autonomy becomes blurry, leading to legal uncertainty. This normative legal research aims to analyze the synchronization of election campaign regulations with university autonomy, as well as to examine the implementation and impact of enforcing neutrality rules. Using Hans Kelsen's Stufenbau Theory and Lawrence Friedman's Legal Effectiveness Theory, this study looks into the tension between the norms of Law No. 7 of 2017 on Elections and Law No. 12 of 2012 on Higher Education. Research results show that there is horizontal antinomy at the law level, which triggers legal dualism. Although the Constitutional Court Decision No. 69/PUU-XXII/2024 has mitigated this tension through conditional campaigns with the Rector's permission, vertical misalignment still occurs in KPU Regulations that contain complicated administrative restrictions, making them materially flawed (lex superior derogat legi inferiori). On the other hand, a total ban on campaigning through college statutes is seen as hierarchical disobedience (normative disobedience). From a legal effectiveness perspective, enforcing neutrality has not been effective and is subordinate due to gaps in the law (leemten in het recht) in the legal substance, overlapping authority between Bawaslu, BKN, and the Rectorate in the legal structure, and the emergence of a chilling effect and self-censorship in the academic community’s legal culture, which will threaten the campus as a laboratory of democracy.